PENGARUH RASIO SOLVABILITAS TERHADAP KINERJA KEUANGAN PADA SEKTOR PERBANKAN DI BURSA EFEK INDONESIA PERIODE 2012 – 2016 - Fitria Fitria (EKONOMIKA SYARIAH : Journal of Economic Studies, 2018)
This research aims to know the magnitude of the influence of Solvency Ratio on performance of the financial of banking sector in the Indonesian stock exchange. The purpose of this research is seen from the problem "how to influence their solvency ratio against the financial performance in the banking sector in Indonesia stock exchange period 2012 – 2016?". Based on the results of the research that has been done, it was found that their solvency Ratios the negative effect on performance on financial sector perbankkan in the Indonesia stock exchange in the period 2012-2016.